2016
DOI: 10.1007/s10096-016-2735-4
|View full text |Cite
|
Sign up to set email alerts
|

Vaccine hesitancy among general practitioners: evaluation and comparison of their immunisation practice for themselves, their patients and their children

Abstract: To gain knowledge about vaccine hesitancy among general practitioners (GPs), we conducted a survey to compare their vaccination attitudes for themselves, their children and their patients. A questionnaire survey was sent to GPs working in private practice in the Rhône-Alpes region, France, between October 2013 and January 2014. GPs' immunisation practices for diphtheria-tetanus-poliomyelitis (DTP), measles-mumps-rubella (MMR), pneumococcal, pertussis, hepatitis B (hepB), human papillomavirus (HPV), seasonal an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 37 publications
1
44
0
1
Order By: Relevance
“…We hypothesize that most GPs are convinced of the efficacy and the safety of this vaccine, since 77% reported that their children were vaccinated, but that barriers prevent some from recommending this vaccine to their patients. Killian et al found in their survey the same finding, since HepB vaccine coverage rate reported by GPs was higher for their children (100%), than for their patients (87%, p <0.001) [12]. Numerous patient-related barriers exist.…”
Section: Interpretation Of the Resultsmentioning
confidence: 63%
See 1 more Smart Citation
“…We hypothesize that most GPs are convinced of the efficacy and the safety of this vaccine, since 77% reported that their children were vaccinated, but that barriers prevent some from recommending this vaccine to their patients. Killian et al found in their survey the same finding, since HepB vaccine coverage rate reported by GPs was higher for their children (100%), than for their patients (87%, p <0.001) [12]. Numerous patient-related barriers exist.…”
Section: Interpretation Of the Resultsmentioning
confidence: 63%
“…To the best of our knowledge, only two studies have examined this topic; the first one, a cross-sectional questionnaire survey conducted by Posfay et al in Switzerland in 2004 found that 93% of the 1017 surveyed physicians (paediatricians and other doctors) agreed with official vaccination recommendations and would apply them to their own children [11]; however, this work did not compare GPs' vaccination behaviour for their patients and their own children. The second one is a very recently published survey conducted in 2013 in one French region, with a low response rate (12.5%), that compared vaccination behaviours of GPs for themselves, their children and their patients [12]. They found that vaccination coverage rates reported by GPs were higher for their children than for their patients for HepB (100% versus 87%), and higher for their patients than for their children for pneumococcal vaccine (90% versus 84%) and HPV vaccine (83% versus 74%).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, since it is well established that HCWs play a role in nosocomial transmission of infectious diseases, the low-level coverage of those susceptible did not contribute to limit the spread of infections and might not provide indirect protection for the patients. The findings of previous investigations showed a higher coverage for several vaccinations in different groups of HCWs compared to the results of this survey, with values of 41.7% [21] and 45.7% [22] for influenza in Slovenia and France, respectively; values of 93.7% and 80.5% were reported for diphtheria-tetanus-acellular-pertussis and measles-mumps-rubella in Italy, respectively [12]; values of 88% and 72% were reported for diphtheria-tetanus-poliomyelitis and pertussis in France, respectively [23]; and a value of 50.5% was reported for pertussis in Australia [24]. One possible explanation for the observed poor immunization coverage could be the lack of free on-site vaccines at work.…”
Section: Discussionmentioning
confidence: 63%
“…Several studies regarding the hesitancy in both parents [18][19][20][21] and in health care workers [22][23][24] have been published, but to the best that we could ascertain no previous research are currently available in Italy regarding childhood vaccine hesitancy among parents. Thus, to address this knowledge gap, the present crosssectional survey was designed to assess the prevalence of vaccine hesitancy and to identify factors associated with vaccine hesitancy among a sample of parents of children aged 2 to 6 years in Italy and the results could be used to target optimal public health strategies to improve overall vaccination coverage.…”
Section: Introductionmentioning
confidence: 96%